Autoridade e autenticidade: um paradoxo kierkegaardiano. - Silva, Adenilton Moises da (2023)
Based on some assumptions of Kierkegaard's thought, this research sought to present a very common conflict in the religious universe, the relationship between the authority principle and the authenticity principle, in evangelical Christianity. This problem is seen as a religious paradox, investigated and rethought through the philosophy of the Danish author. In order to accomplish this epistemological task, we use Danish Christian-existentialist philosophy as a reading key, through which it is possible to dialogue with theoreticians from the sociology of religion and theology: Peter Berger, Danièle Herviue-Léger, Leonardo Boff, etc. These theoretical contributions show an interdisciplinarity capable of promoting a dialogue pertinent to the field of the Sciences of Religion. Ingesting the performaces of religious institutions in contemporary times, as well as the practices of the faithful, helps to have a better profile of the evangelical field, especially its strategies used as a form of convincing, based on a political-religious discourse, where the procedures for the Church-State concession are implicit. By means of this political-religious alliance, the concepts "triumphant church" and "militant church" are invested in, in order to present the divergences and uncopatibilities of the political-religious discourse produced by political and/or religious authorities. Having discussed this scenario, the thesis will propose a categorical religious imperative: "you must love your neighbor" as a condition to overcome the religious conflict between the authority principle and the authenticity principle, suggesting that service, that is, christian works, equalizes everyone's life, breaking the differences founded on authoritarianism and christian comfort.